Rethinking Music - Cook, Nicholas; Everist, Mark (Oxford New York Oxford University Press, 1999)
Rethinking Music offers a comprehensive re-evaluation of current thinking about music. In this book, 24 distinguished musicologists, music theorists, and ethnomusicologists review different dimensions of musical study, revealing a range of concerns that are shared across the discipline: the nature of musicological practice, its social and ethical dimensions, issues of canon and value, and the relationship between academic study and musical experience.
Keywords: Music philosophy and esthetics